Rhodococcus opacus B4: a promising bacterium for production of biofuels and biobased chemicals - Castro, Ana Rita (2016)
Bacterial lipids have relevant applications in the production of renewable fuels and biobased oleochemicals. The genus Rhodococcus is one of the most relevant lipid producers due to its capability to accumulate those compounds, mainly triacylglycerols (TAG), when cultivated on different defined substrates, namely sugars, organic acids and hydrocarbons but also on complex carbon sources present in industrial wastes. In this work, the production of storage lipids by Rhodococcus opacus B4 using glucose, acetate and hexadecane is reported for the first time and its productivity compared with Rhodococcus opacus PD630, the best TAG producer bacterium reported. Both strains accumulated mainly TAG from all carbon sources, being influenced by the carbon source itself and by the duration of the accumulation period. R. opacus B4 produced 0.09 and 0.14 g L1 at 24 and 72 h, with hexadecane as carbon source, which was 2 and 3.3 fold higher than the volumetric production obtained by R. opacus PD630. Both strains presented similar fatty acids (FA) profiles in intact cells while in TAG produced fraction, R. opacus B4 revealed a higher variability in fatty acid composition than R. opacus PD630, when both strains were cultivated on hexadecane. The obtained results open new perspectives for the use of R. opacus B4 to produce TAG, in particular using oily (alkane-contaminated) waste and wastewater as cheap raw-materials. Combining TAG production with hydrocarbons degradation is a promising strategy to achieve environmental remediation while producing added value compounds.